Bought and Lost: Perlindungan Hukum bagi Konsumen atas Kehilangan Aset Digital di Era Metaverse - Putra, Ismail Rangga Wahana; Lie, Gunardi; Sihite, Jelita (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
The rapid development of digital technology has given rise to new phenomena such as the metaverse and virtual marketplaces, which offer both opportunities and challenges for consumers in Indonesia. On the one hand, consumers can benefit from the ease of conducting digital asset transactions such as cryptocurrencies, NFTs, and various forms of virtual goods. On the other hand, they face serious risks, including financial losses, privacy violations, exploitation through microtransactions, and legal uncertainty when dealing with foreign business actors. This study aims to analyze consumer protection in digital asset transactions within the metaverse and virtual marketplaces, identify the risks faced by consumers, assess the adequacy of Indonesia’s current regulations, and review international practices as references. The research employs a normative legal approach combined with qualitative analysis by examining statutory regulations, legal literature, and relevant national and international journals. The findings reveal that although Indonesia has enacted the Consumer Protection Law and the Personal Data Protection Law, these regulations have not specifically addressed consumer protection in the metaverse and virtual marketplace context. As a result, consumers remain vulnerable to various digital transaction risks. The study implies the need for adaptive regulations, stronger digital transaction supervisory institutions, and the adoption of international practices such as the European Union’s General Data Protection Regulation (GDPR) to ensure more comprehensive consumer protection in Indonesia.